Depression, Anxiety and Stress among Vitiligo Patients and Healthy Controls at A Tertiary Hospital: A Comparative Cross-Sectional Study - Parajuli, Sudip; Tulachan, Pratikchya; Khadka, Anupa; Mishra, Vilok (Journal of Institute of Medicine Nepal, 2025)
Introduction Vitiligo is often associated with stigma, leading to emotional distress and increased vulnerability to mental health disorders such as depression, anxiety, and stress. This study aimed to compare the levels of these psychological issues between vitiligo patients and healthy controls, while also examining the impact of socio-demographic and clinical factors. Methods This hospital-based cross-sectional study included 42 vitiligo patients and 42 healthy controls. The Vitiligo Area Scoring Index (VASI) was used to assess the severity of vitiligo, and the Depression Anxiety Stress Scale (DASS-21), comprising three subscales: Depression (DASS-D), Anxiety (DASS-A), and Stress (DASS-S), was used to evaluate depression, anxiety, and stress. Descriptive statistics and non-parametric tests were used for data analysis. Results Among vitiligo patients, 50% (n=21) exhibited depressive symptoms [median DASS-D score 9 (IQR 1.5-18.0)], compared to 19% (n=8) of controls. Anxiety symptoms were present in 54.8% (n=23) of the vitiligo group [median DASS-A score 8 (IQR 2.0-16.5)], compared to 21.4% (n=9) of controls. Stress was reported in 31% (n=13) of the vitiligo group [median DASS-S score 11 (IQR 2.0-16.5)], compared to 7.1% (n=3) in controls. Significant differences were found in depression, anxiety, and stress between the two groups (p = 0.005, p = 0.003, p = 0.02). A negative correlation between vitiligo duration and anxiety/stress was observed (p=0.03, p=0.01). Positive correlations existed among the DASS-D, DASS-A, and DASS-S scores. Conclusion Patients with vitiligo were more susceptible to psychological distress, including symptoms of depression, anxiety, and stress, and experienced these issues at significantly higher rates compared to healthy controls.